Synthesis and characterization of alkaline‐soluble triazine‐based poly(phenylene sulfide)s with high refractive index and low birefringence. Issue 7 (4th January 2018) - Fu, Mao‐Chun; Murakami, Yoshitaka; Ueda, Mitsuru; Ando, Shinji; Higashihara, Tomoya
ABSTRACT: High‐refractive‐index (high‐ n ) polymers (HRIPs) with a high optical transparency are highly needed in advanced optoelectronic devices. In this work, we report the synthesis and characterization of a series of high‐ n, transparent, totally colorless, and high‐sulfur‐containing poly(phenylene sulfide)s (PPSs) bearing a triazine unit. Two new triazine monomersT1 andT2 with hydroxyl and tert ‐butyl acetate side chains, respectively, were designed and synthesized to develop PPSs with high‐ n and high alkaline solubility. These PPSs were prepared by the single‐phase polycondensation fromT1 /T2 and commercial aromatic dithiols such as 4, 4′‐thiobisbenzenethiol (TBT ) and benzene‐1, 3‐dithiol (BDT ), achieving very high‐ n up to 1.7530 at 633 nm, a high optical transparency ( T % > 90% @400 nm) and low birefringence (Δ n  = 0.0014–0.0080), and exhibiting high potential on the application of high‐ n photoresists. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 724–731 Abstract : For the future application of high‐ n photoresists, a series of poly(phenylene sulfide)s (PPSs) was synthesized successfully from triazine derivatives and aromatic dithiols by single‐phase polymerization, exhibiting high‐ n values (1.6448–1.7530), high transparency ( T % > 90% @400 nm), low birefringence values (Δ n  = 0.0014–0.0080), and good alkaline solubility.